2017
DOI: 10.1002/qj.3165
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐scale analysis of the extreme rain event of Ouagadougou in 2009

Abstract: This study presents a multi‐scale analysis of an extreme rain event that occurred in Burkina Faso on 1 September 2009 with an absolute record of 263 mm rainfall observed at Ouagadougou. This high‐impact weather system results from the combination of several favourable ingredients at different scales. The sea‐surface temperature anomaly patterns in July–August 2009 of both the Atlantic cold tongue, the Tropical Atlantic Dipole and the Mediterranean Sea are favourable factors for the northward penetration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 71 publications
4
49
0
Order By: Relevance
“…Crétat et al [24] found that intense rainfall events (percentile approach) occurring over West Africa west of 8 • E are clearly related to active 3-5-day AEWs in both observations and regional climate simulations. Case studies of extreme rainfall events are available for Ouagadougou in Burkina Faso [25,26] and Abakaliki in Nigeria [27] which show that the rains are associated with the passage of MCS, exceptionally high atmospheric moisture and a lower-tropospheric vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Crétat et al [24] found that intense rainfall events (percentile approach) occurring over West Africa west of 8 • E are clearly related to active 3-5-day AEWs in both observations and regional climate simulations. Case studies of extreme rainfall events are available for Ouagadougou in Burkina Faso [25,26] and Abakaliki in Nigeria [27] which show that the rains are associated with the passage of MCS, exceptionally high atmospheric moisture and a lower-tropospheric vortex.…”
Section: Introductionmentioning
confidence: 99%
“…This study will focus specifically on the effect of tropical waves on important components of the WAM such as the monsoon layer, inter-tropical discontinuity (ITD, Lélé and Lamb 2010) position, Saharan Heat Low (SHL, Lavaysse et al 2009; and AEJ. Additional attention is paid to the conditions for organized convection in form of mesoscale convective systems (MCSs, Houze 2004), which are responsible for the majority of rainfall in West Africa (Eldridge, 1957;Laing et al, 1999;Fink and Reiner, 2003) and commonly cause extreme precipitation (Engel et al, 2017;Lafore et al, 2017). In order to make use of as much data as possible in this data scarce region, reanalysis data and insitu measurements by radiosondes will be compared.…”
Section: Introductionmentioning
confidence: 99%
“…MCSs are often organized in squall lines propagating from east to west. Under particular conditions, organized convective systems can be stationary (long‐lasting systems) and may produce large rainfall amounts over a particular location (Lafore et al, ). Local convection can also occur, but this generally produces less rainfall.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A first option to that end is to make an analytic approach similar to that proposed by Taylor et al (), including the analysis of regional contrasts in storm properties within the Sahel. A second possibility is to extend the case studies of extreme events such as Lafore et al () in Ouagadougou to other locations in the Sahel (see, e.g., Engel et al, ). Atmospheric simulation experiments, in particular high‐resolution convection‐permitting simulations, could also be very helpful to find some physical explanations of the observed trends in the co‐occurrence of extremes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%